PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DIMEDIASI OLEH KEPUASAN PELANGGAN (Studi Pada Kedai Kopi Kembang, Malang) - NICKO ALFIAN ; Dr. Mugiono, SE.,MM.,CMA
The type of research used is explanatory research. This study used 150_x000D_ samples. Sampling using non-probability sampling technique with purposive_x000D_ sampling method. Reviews from visitors to Kedai Kopi Kembang Malang who_x000D_ have visited at least 2 times. The method of data analysis in testing instruments_x000D_ using the SmartPLS version 2.0 model through the stages of outside model_x000D_ analysis, internal models, and hypothesis testing. _x000D_ The results showed that: (1) service quality has a positive effect on_x000D_ customer loyalty, (2) service quality has a positive effect on customer satisfaction,_x000D_ (3) customer satisfaction has a positive effect on customer loyalty, (4) service_x000D_ quality has a positive effect on customer loyalty mediated by customer_x000D_ satisfaction. _x000D_ _x000D_ Keywords: Service Quality, Costumer Satisfaction, Costumer Loyalty.